Energy harvesting from dynamic vibration pendulum absorber - Malaji, P.; Rajarathinam, M.; Jaiswal, V.; Ali, S.; Howard, Ian (2019)
© 2019, Springer Nature Singapore Pte Ltd. Dynamic vibration absorbers (DVAs) have proven to be an effective passive technique to suppress device vibration, with many realistic implementations in structures, buildings, and machines. Vibration energy harvesting is a process used to convert unwanted vibrations of a host structure into electrical energy. In this paper, a harmonic single degree-of-freedom system is considered consisting of a pendulum absorber and electromagnetic energy harvesting transduction mechanism. These types of DVAs are suitable for control of multi-story buildings, where for the simplicity of analysis a two degree-of-freedom system which models the building with the absorber is considered. Controlling the vibrations of buildings is the primary objective, and harvesting the energy from the dynamic vibration pendulum absorber at the same time is the secondary objective. Parametric analyses are performed. It is observed that proper system parameter selection is key for reducing the vibration amplitude of the primary system and for enhancing the energy harvested from the secondary system. Optimization analysis based on the genetic algorithm approach is used to optimize the system parameters. It is observed that with a proper selection of parameters, wideband energy can be harvested along with reduction in vibration of the building.